STUDI TENTANG PELEMBAGAAN SUBSTANSI BUDAYA ORGANISASI DALAM KONSEP LEARNING ORGANIZATION - Salabi, Agus Salim; Prasetyo, Muhammad Anggung Manumanoso (Reflektika, 2022)
The educational agenda's long-term viability and suitability for institutional revitalization efforts are still being debated. To address the issue of educational institutions, a new conceptual framework model is required. The concept of organizational development via the concept of learning organization is already numerous and well-established. As a result, the study seeks to understand the governance model of long-term learner organizations that have been thoroughly examined in terms of organizational culture. The descriptive survey method was used for qualitative research. The study's findings revealed five essentials in the implementation of the learner school concept, namely the creation of an educational environment, the enhancement of institutional independence, the succession of learner leadership, and the caderization program as evidence of the institution's sustainability guarantee. Several school programs, including extracurricular activities, school literacy movements, habitation activities, and spontaneous behavior, reflect the cultural actualization of organizations. Managers' commitment to education is recommended by the study's findings in order to remain sustainable; community participation is optimized, with a focus on aspects of data inventory, planning, implementation, monitoring, and evaluation of programs, and optimization of community participation by being supported by Local Governments, including stakeholders. The practical implications of learner concepts create broader and more transformative cultural values that reflect the 21st century's complex challenges and the need for structural reform in sustainable organizations.